Meritokrasi VS Politisasi Jabatan Karir dalam Birokrasi Lokal: Sebuah Paradoks Netralitas Birokrasi - Edison Edison (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2011)
This paper attempts to assess various initiatives tailored toward strengthening bureaucratic reform at the local level. Some of the problems which characterize local bureaucracies include low professionalism, domineering influence of local government beads and politicians on key positions in the local bureaucracy. Though not new, the issue is still not accorded the attention it deserves. With respect to relations of the local government heads bureaucracy, there has emerged a tendency of diluting the bureaucratic culture, which has a become more common in the wake of the implementation of government policy in Act No. 32/ 2004 on local government, which allows direct election of local government heads. Professional bureaucracy emphasizes the importance of legal-rational system of meritocracy. Consistency of merit system should promote fair competition for all. However, the intervention of the local government executives in appointing career members of the local bureaucracy who assume structural position, has hampered efforts at improving the professionalism ideal. Worse still, incumbent local government heads have undermined the neutrality of the local bureaucracy by filling important positions with handpicked political supporters. To that end, bureaucracy in many regions is increasingly being filled with bureaucrats who share affiliations with local government heads. Inevitably, cleavages in the bureaucracy have emerged as fractions are formed that support and appose the incumbent local government head. Consequently, discrimination in treatment occurs within the bureaucracy, which culminates into the promotion and demotion of personnel on the basic of affiliation rather than merit and capability. Enhancing professionalism in the bureaucracy calls for effort to ensure that high ranking officials in the bureaucracy be free from intervention from political pressure groups or politicians officials.